2013
DOI: 10.1002/app.39126
|View full text |Cite
|
Sign up to set email alerts
|

Properties of crosslinked polyurethanes obtained by acrylic side‐group polymerization and of their blends with various plant oils

Abstract: Novel polyurethane elastomers have been developed to incorporate plant oil into their matrix. Bisphenol A glycerolate diacrylate was used as a chain extender for the polyurethane prepolymer obtained from poly(tetramethylene oxide) glycol and 1,6hexane diisocyanate. The curing of the polyurethane acrylate matrix in the presence of the plant oil results in a network matrix which includes renewable resources in their structure. The effects of the inclusion of different vegetable oil (such as soybean oil, rapeseed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…From the data, it is observed that contact angle slightly increases as crosslink density of cured films increases from the cured system. However, the major factor governing the contact angle was the hydrophobic nature of vegetable oil in all these cured films and the results are comparable to other vegetable oil based PU coatings …”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…From the data, it is observed that contact angle slightly increases as crosslink density of cured films increases from the cured system. However, the major factor governing the contact angle was the hydrophobic nature of vegetable oil in all these cured films and the results are comparable to other vegetable oil based PU coatings …”
Section: Resultssupporting
confidence: 77%
“…However, the major factor governing the contact angle was the hydrophobic nature of vegetable oil in all these cured films and the results are comparable to other vegetable oil based PU coatings. 34,36 WA of the polymer is directly related to their free volume fraction, chemical composition, crosslink density, and presence of polar groups capable to form hydrogen bonds with water molecules. The results of WA test are mentioned in Table III.…”
Section: Physicochemical Properties Of Mahua Oil Mfa and Polyetheramentioning
confidence: 99%
“…One of the most frequently used renewable raw materials are cashew nut shell liquid for getting polyols . Vegetable oil has also been blended to prepared polyols as a starting material for Pus . Petrovic et al have reported the preparation of rigid type PUs from soybean oil .…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Vegetable oil has also been blended to prepared polyols as a starting material for Pus. 14,15 Petrovic et al have reported the preparation of rigid type PUs from soybean oil. 16 There are several reports available on the PUs based on soybean oil, castor oil, nahar seed oil, rape seed oil, and plam oil.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal stability of 20 and 25 wt% TFFA-based polymer is higher than 5, 10, and 15 wt% TFFA-based polymer between the temperatures 250-380°C, due to the higher crosslinking The crosslinking increases the thermal stability of the polymer. 26,27 The disruption of urethane bonds causes decomposition of hard segments and thermally stable amide linkages correspond to the temperature 280-320°C. 28,29 Gloss of UV-cured coating…”
Section: Thermogravimetric Analysis Of Uv-cured Filmsmentioning
confidence: 99%